SOX4 is overexpressed in diffusely infiltrating astrocytoma and confers poor prognosis. Issue 6 (12th June 2015) - Li, Ling; Li, Qiuyao; Chen, Xueqin; Xu, Miao; Li, Xinglan; Nie, Ling; Chen, Ni; Gong, Jing; Mao, Qing; Zhou, Qiao
Abstract : The SOX4 (sex‐determining region Y‐related high‐mobility‐group box transcription factor 4) gene plays critical roles in embryonic development and cell‐fate determination. Recently, SOX4 overexpression has been found in various tumors. However, its expression status and prognostic significance in astrocytoma remain unknown. In this study, SOX4 expression in diffusely infiltrating astrocytoma (WHO grades II‐IV) tissues (in comparison with pilocytic astrocytomas) was examined by immunohistochemistry, and its relevance with prognosis was analyzed. Our data showed that SOX4 was over‐expressed in diffusely infiltrating astrocytomas and its expression was positively correlated with astrocytoma grade (WHO grades II‐IV). Significantly, Kaplan‐Meier analysis revealed that SOX4 nuclear overexpression (SOX4‐N) was associated with poorer progression‐free survival (PFS) and disease‐specific survival (DSS) in diffusely infiltrating astrocytoma patients ( P < 0.05). Cox regression analysis further showed that nuclear SOX4‐N was a significant independent negative prognostic factor for these patients.